EFEKTIFITAS PENYALURAN KREDIT USAHA RAKYAT (KUR) TANI BNI CABANG BOJONEGORO MELALUI KINERJA COLLECTION AGENT (CA) TERHADAP PRODUKTIFITAS PETANI - jurnalmap map; Muhammad Haris Romadloni Syukron; Hadi Susanto; Arini Sulistyowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The purpose of this study is to describe the effectiveness of the distribution of KUR Tani which consists of five aspects, namely aspects of program targets accuracy, aspects of timeliness, aspects of the accuracy of the amount of money received by customers, aspects of credit load accuracy and aspects of procedure accuracy and farmer productivity and Collection performance Agent (CA). This type of research is explanatory research and the approach in this study uses a quantitative approach. The population in this study were all customers who used the KUR Tani program at BNI Bojonegoro Branch, which were recorded accumulatively until September 2019, amounting to 4085 people. The sampling technique uses the Simple Random Sampling method with the calculation of the Slovin formula obtained a sample of 98 customers. Data analysis uses path analysis. The results showed that the effectiveness of KUR Tani distribution consisting of 5 aspects above directly affected the performance of Collection Agent (CA) in Bojonegoro Regency. Only aspects of the accuracy of the program's objectives do not significantly influence the Performance Collection Agent (CA).Keywords: effectiveness, performance, productivity